Studi Analisis Metodologi Tafsir Mafatih Al-Ghayb Karya Fakruddin Al-Razi - Alam Tarlam (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI Miftahul Huda Subang, 2023)
The belief of Muslims that the Qur'an is a holy book that will be eternal for all time has turned out to be one of the reasons in itself why the interpretation and exploration of the meaning of the Qur'anic verses is the task of the people that never ends. Interpretation as an effort to understand and explain the meaning of the content of the Qur'an has undergone quite varied developments. Fakhrudin ar-Razi is one of the Muslim thinkers who participated in contributing his knowledge to the treasures of the world of interpretation. This article was written to find out and analyze the methodology contained in the interpretation of mafatih al Ghayib by Fakruddin al Razi. The writing method in this article uses a descriptive analytic method based on the literature. As for the results of this study, the bi al-Ra'yi interpretation method describes an interpreter of the Qur'an adhering to his ijtihad, not adhering to the asar taken from his companions. who want to interpret the Qur'an.